Railway Interlockings – A Review of the Current State of Railway Safety Technology in Europe - Bădău, Florin (Promet - Traffic&Transportation, 2022)
Interlockings are an essential element of the railway system. They are necessary to command and control devices, such as points and signals in order to route trains within the bounds of railway stations. Their design must ensure the highest level of safety for all involved parties. The European continent has an extensive railway network which has slowly grown over more than 150 years. Interlockings have evolved over the same period from large mechanical devices requiring physical force to operate to computerised systems capable of complex operations. Despite the technological leap, many interlockings using older technologies are still in use in the present. This review aims to paint an accurate picture of the current state of interlockings in Europe by evaluating the share of each interlocking generation (mechanical, relay and electronic). The study covers 15 countries and over 200,000 km of railway tracks, representing over two thirds of the entire EU railway network. A brief presentation is given for each country, while comparisons made between the researched countries highlight certain key findings. The focus is only on station interlockings, not including line signalling. The conclusions of this analysis include recommendations for current and future development of the railway sector.